Implementation of a Waste Bank Website using the Agile Scrum Approach and User Acceptance Testing (UAT) - Muhammad Arifin Dava; Putut Pamilih Widagdo; Muhammad Rivani Ibrahim (Universitas Islam Indragiri, 2026)
Waste management in Indonesia continues to face significant challenges, largely due to manual record-keeping practices that often lead to data duplication, reporting delays, and a lack of transparency. This study develops EcoHub, an integrated digital dashboard designed to monitor waste deposit flows, point conversion, and product transactions to support a circular economy ecosystem. The research addresses a gap in the limited availability of waste bank systems that integrate deposit management, e-wallet functionality, and e-commerce within a unified platform. By adopting the Agile Scrum approach, the system is designed to adapt to user needs through short development iterations and continuous evaluation. The testing results indicate that all system functionalities operate effectively, with a user acceptance rate (UAT) of 89.17%, categorized as Very Good. The novelty of this study lies in the direct integration between waste deposits and real economic exchange mechanisms, which has been shown to significantly enhance operational efficiency for various stakeholders while improving transparency in waste bank management.